2019
DOI: 10.1016/j.ijme.2019.100312
|View full text |Cite
|
Sign up to set email alerts
|

What factors influence student satisfaction with module quality? A comparative analysis in a UK business school context

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
2
21
0
1
Order By: Relevance
“…It was found that the survey items related to “Teaching” was of significant influence, such as “Staff are good at explaining things,” “Staff have made the subject interesting,” and “Staff are enthusiastic about what they are teaching,” with the first item being particularly important ( Langan and Harris, 2019 ), showing that the teacher and teaching factors are always more important than the learner factors. Besides, based on econometric modeling of 21,096 undergraduate student responses and 4,429 postgraduate student responses to the module evaluation questionnaire, Sutherland et al (2019) found that the helpfulness of lectures and seminars provided by teachers, involving direct student-teacher contact time, is the most significant influencing factor of OLS. Similarly, in a large scale study of learning satisfaction of 16,670 new and 99,976 continuing students, Li et al (2017) found that learners’ satisfaction with the assessment as well as advice and guidance provided by instructors were key factors influencing OLS of both new and continuing students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the survey items related to “Teaching” was of significant influence, such as “Staff are good at explaining things,” “Staff have made the subject interesting,” and “Staff are enthusiastic about what they are teaching,” with the first item being particularly important ( Langan and Harris, 2019 ), showing that the teacher and teaching factors are always more important than the learner factors. Besides, based on econometric modeling of 21,096 undergraduate student responses and 4,429 postgraduate student responses to the module evaluation questionnaire, Sutherland et al (2019) found that the helpfulness of lectures and seminars provided by teachers, involving direct student-teacher contact time, is the most significant influencing factor of OLS. Similarly, in a large scale study of learning satisfaction of 16,670 new and 99,976 continuing students, Li et al (2017) found that learners’ satisfaction with the assessment as well as advice and guidance provided by instructors were key factors influencing OLS of both new and continuing students.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous empirical research on OLS collected data overwhelmingly through a combination of relatively smaller scale questionnaires and interviews, which may influence the validity of the research findings. To have a full and deeper understanding of OLS, an increasing number of large(r) scale studies are suggested to be conducted in future, with reference to some pioneering studies using large scale data ( Li et al, 2016b , 2017 ; Langan and Harris, 2019 ; Sutherland et al, 2019 ). It is also suggested that future studies might be integrated with techniques applied in cognitive neuropsychology, such as magnetoencephalography, electroencephalography and eye tracking technology, to obtain more scientific research conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Improving direct student–teacher contact time has been reported to be a factor influencing the student satisfaction. [ 24 ] As many students reported stress, anxiety, and depression, counseling and psychological support in the campus are expected to be helpful. Sessions related to healthy relationship, stress management, and supporting nonacademic and extracurricular skills of students may improve positive experience which may build student confidence and bolster performance.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the research, students express satisfaction when they observe that the lecturers come "…to be knowledgeable, enthusiastic, approachable, and friendly.." (Voss, Gruber, & Szmigin, 2007). Student satisfaction can be determined by another criteria, where"….the helpfulness of lectures and seminars, involving direct studentteacher contact time, is the most important determinant of satisfaction…" (Sutherland, Warwick, & Anderson, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%